The impact of referendums on the centralisation of public goods provision: a political economy approach - Schnellenbach, Jan; Feld, Lars P.; Schaltegger, Christoph A. (Economics of governance, 2010)
The paper compares decision-making on the centralisation of public goods provision in the presence of regional externalities under representative and direct democratic institutions. A model with two regions, two public goods and regional spillovers is developed in which uncertainty over the true preferences of candidates makes strategic delegation impossible. The political economy argument against centralisation of Besley and Coate (J Public Econ 87:2611-2637, 2003) does therefore not apply. Instead, it is shown that the existence of rent extraction by delegates alone suffices to make cooperative centralisation more likely through representative democracy under reasonable assumptions. In the case of non-cooperative centralisation, the more extensive possibilities for institutional design under representative democracy increase the likelihood of centralisation. Direct democracy may thus be interpreted as a federalism-preserving institution.
Online veröffentlicht am 27. Juni 2009
Gesehen am 27.06.2023